1993
DOI: 10.1177/019459989310800308
|View full text |Cite
|
Sign up to set email alerts
|

Hearing Levels of Patients with Otosclerosis 10 Years after Stapedectomy

Abstract: Hearing levels of 174 patients (213 ears operated on) with otosclerosis undergoing stapedectomy were analyzed. All patients had followup of 10 years or more, the mean follow-up period being 13.4 years. Eighty-seven ears (41%) underwent posterior crus stapedectomy, and in the remaining 126 ears (59%) a prosthesis was inserted. Large fenestra technique was used in all cases. In the long run, both air conduction and bone conduction thresholds of ears operated on showed remarkable deterioration from the best value… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

1997
1997
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 9 publications
1
9
0
Order By: Relevance
“…This is in accordance with that reported earlier. [4,5] The mean air-bone gaps at speech frequency that is 500, 1000, and 2000 Hz were calculated in both the groups in preoperative as well as in postoperative periods. It was observed that both the groups had marked improvement in their respective follow-up periods.…”
Section: Discussionmentioning
confidence: 99%
“…This is in accordance with that reported earlier. [4,5] The mean air-bone gaps at speech frequency that is 500, 1000, and 2000 Hz were calculated in both the groups in preoperative as well as in postoperative periods. It was observed that both the groups had marked improvement in their respective follow-up periods.…”
Section: Discussionmentioning
confidence: 99%
“…Aarnisalo et al (22) observed that although there was an average reduction of 0.9 dB per year in both AC and BC thresholds during 20 years after stapes surgery (either with stapedotomy or stapedectomy), the ABG only increased by 2 to 4 dB during this period. Vartiainen et al (24) noted that the mean BC thresholds of otosclerotic ears that were surgically treated deteriorated during 10 years of follow-up. The study of Spandow et al (3) did not support these findings of a deterioration of BC thresholds.…”
Section: Discussionmentioning
confidence: 99%
“…Reported success rates for experienced surgeons have been high(up to 97%), 1,2 while complications such as a dead ear (0.6% to 3%) 3‐5 have been low. Although hearing levels in otosclerotic ears can gradually worsen over time, they generally remain better for operated ears than for nonoperated ears 6 . The onset of a hearing loss due to otosclerosis usually begins with a conductive loss in the low frequencies and progresses to a larger flat conductive loss as the footplate becomes completely fixed.…”
Section: Introductionmentioning
confidence: 99%
“…Although hearing levels in otosclerotic ears can gradually worsen over time, they generally remain better for operated ears than for nonoperated ears. 6 The onset of a hearing loss due to otosclerosis usually begins with a conductive loss in the low frequencies and progresses to a larger flat conductive loss as the footplate becomes completely fured. Some otosclerotic patients retain a small conductive hearing loss for years while others progress rapidly to a larger loss.…”
Section: Introductionmentioning
confidence: 99%